The impact of task-oriented training on frailty among post-cancer victims – a pilot study - Elango, Jayadharshini; Vishnuram, Surya; Abathsagayam, Kumaresan (Medycyna Paliatywna/Palliative Medicine, 2025)
Cancer survivors experience particular health issues as a result of their diagnosis and the effects of treatment on physical function. Frailty is widespread in cancer survivors, and it leads to increased disability, poor physical functioning, hospitalisation, and death. Frailty is caused by a reduction in functional mobility and strength, which impacts quality of life. A task-oriented approach is an activity-centred method in which a task is repeatedly trained to improve functional performance. Thus, the purpose of the study is to identify an effective intervention that minimises frailty by improving functional mobility and strength. In this study, 35 participants were enrolled based on the inclusion criteria. Pre-test evaluation for functional mobility and strength were measured using the time up and go (TUG) test and the 5 times sit to stand test (5XSTS). Interventions were taskoriented training (TOT) and strengthening exercises following which post-intervention evaluation was done. Following the descriptive statistical analysis, pre-test values of the 5XSTS and TUG test were 28.8 ±3.67 and 19.8 ±2.65, and the mean post-test values of the 5XSTS and TUG test were 20.4 ±3.11 and 15.4 ±2.67. From the results, it can be seen that there is a significant difference in p-values (< 0.001) regarding functional mobility and strength. The study suggested that TOT along with strength training helps to improve functional mobility and strength thereby improving frailty among cancer survivors.